Energy intake and energy requirement of overweight non-smoking men during the covid-19 pandemic lockdown 2.0 - Sharan, Nursharlina (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Objective: This research was conducted to predict the best factors contributed to energy intake and energy requirement and association with dietary intake, body composition and energy availability among overweight non-smoking men during COVID-19 pandemic lockdown 2.0. Method: Thirty-six overweight sedentary non-smoking men aged 25 ± 7 years old, body weight 82 ± 15 kg and body mass index 29 ± 5 kg/m2 were recruited in this cross-sectional study. Physical Activity Readiness Questionnaire (PAR-Q), 24-hours dietary intake, and body composition were recorded. Body fat percentage was measured by using the equation by Gomez-Ambrosi et al.(2012), while fat free mass was measured by using equation from Van Itallie et al.(1990). In addition, energy expenditure was calculated by using revised-Harris Benedict equation formula (Roza & Shizgal, 1984: Ismail et al., 1998). The prediction of the best factor contributes to metabolic syndrome either 24-hour dietary intake, body composition (weight, height, body fat percentage and fat free mass) or energy expenditure among overweight non-smoking men is determined by using the Stepwise Linear Regression. Results: The findings show that, non-smoking men body weight and body fat percentage were 82 ± 15 kg and 27 ± 7 %, respectively and they were all categorised as overweight. Their mean energy intake was 2181 ± 587 kcal/day which considered as normal, and their energy expenditure was 373 ± 41 kcal/day which resulted in positive energy balance. The threshold level of energy availability was 30 ± 10 kcal/kg FFM/day which was lower than normal value. Body weight (r= 0.977, p= 0.000), height (r= 0.553, p= 0.000), BMI (r= 0.863, p= 0.000), body fat percentage (r= 0.835, p= 0.000) and fat free mass (r= 0.958, p= 0.000) were positively associated with energy expenditure. Furthermore, there were no significance association between physical activity level, energy intakes and energy availability with energy expenditure. However, body weight was found to be the best predictor to influence energy expenditure. In this study, there was also no association between the energy availability with physical activity level since the participants are physically inactive.